The effect of basalt fiber use on the unconfined compressive strength of low plasticity clay - Gürocak, Zülfü; Aslan Topçuoğlu, Yasemin (Gumushane University, 2023)
Different additives are used in reinforcement processes, called stabilization, which are made to increase the strength of low strength clays. Fibers are the most widely used of these materials. In recent years, the use of fibers in the reinforcement of soils has attracted the attention of researchers as an alternative to traditional chemical stabilization methods, due to their low cost, high strength and easy accessibility. The use of basalt fibers, which are different types of fibers, is increasing due to their economic and environmental friendliness. The aim of this study is to investigate the effect of basalt fiber on the strength of kaolin clay. In order to examine the changes in the strength of the soil by adding basalt fiber in different proportions (0, 1, 2 and 3 % by dry weight) to the soil with different water contents (20, 25, 30 and 35%), unconfined compressive tests were carried out. After the experimental studies, it was determined that the unconfined compressive strength was maximum as a result of the addition of 25% water and 1% basalt fiber to the clay. According to the results of the study, the fiber ratio and the water ratio have a great effect on a successful reinforcement. © 2023, Gumushane University. All rights reserved.
Bazalt fiber kullanımının düşük plastisiteli kilin serbest basınç dayanımı üzerindeki etkisi
Keywords: Basalt fiber; Kaolin clay; Reinforcement; Strength